CLINICAL AND MORPHOLOGICAL ASSESSMENT OF THE EFFECTIVENESS OF THE AMBULATORY HYSTEROSCOPIC MYOMECTOMY - Сафронов, Олег Владимирович; Казачкова, Элла Алексеевна; Казачков, Евгений Леонидович; Сафронова, Ирина Владимировна; Мшак-Манукян, Гоар Норайровна (Mother and Baby in Kuzbass, 2022)
The aim of the research – clinical and morphological assessment of the effectiveness of the ambulatory hysteroscopic myomectomy with diode laser radiation in the pulsed mode in case of submucous uterine myoma. Materials and methods. A comparative analysis of the specific features of the surgery course, post-surgery period, endometrium status and reproductive function has been performed in 171 patients (1st group) who underwent surgery with the use of the diode laser in the pulsed mode and 31 patients (2nd group) who were treated with the use of the bipolar electric energy. Results. Surgeries performed with the use of the diode laser energy in the pulsed mode are characterized by less blood loss in case of single-step and in performing the 1st step of the two-step myomectomy, by complete removal of the uterine myoma in statistically significantly greater number of patients with the uterine myoma of the G2 type (85.96 %) and G1 type with the diameter 7-20 mm (88.89 %), and by absence of the intra- and post-operative complications. Statistically significantly greater number of patients treated with the use of the laser energy show absence of morphological signs of the endometritis (46.78 %) in 2 months after the myomectomy, and of the manifestations of perivascular fibrosis in the endometrium in 5 months (72.0 %). Patients who have underwent surgery with the use of the laser energy in contrast to the women who have been treated with the bipolar electric energy, are characterized by a shorter lapse of time between the surgery event and conception – 7.82 ± 1.42 and 13.13 ± 4.97 months respectively; the frequency of the pregnancy occurrence is 60.78 % and 59.26 %, delivery at term – 95.45 % and 92.31 %. Conclusion. Hysteroscopic myomectomy with the use of diode laser energy in the pulsed mode is effective and safe approach to the removal of the submucous uterine myoma and could be used in ambulatory setting.